Investigation of Performance and Emission on a Single Cylinder Di-Diesel Engine with a Catalytic Conveter Using Bio-Diesel - Surakasi Raviteja, Y S Ratnakar, Ch Polayya, B Ranjan Kumar, VV Prasanna Kumar (International Journal of Modern Agriculture, 2021)
There are approximately 700 million cars on the road every day in the world today, with that number expected to rise to close to 1300 million by 2030. This rise in vehicle numbers would deplete diesel, which is a nonrenewable source of energy and one of the main fuels used to power automobiles. Incomplete combustion products such as CO, HC, NOx, particulate matter, and others result from incomplete combustion in the engine. Several alternate systems are being considered to minimise diesel consumption and emissions, such as advanced engine configuration, fuel pretreatment, fuel additives, exhaust treatment and better combustion process tuning. Biodiesel is the best way to minimise diesel usage and to control automotive exhaust emissions among all forms of technology so far produced, both as a diesel replacement and catalytic converters based on noble group metals. This project deals with bio-diesel processing, mixing of the two combustibles to make mixtures and mixing characteristics as well as vehicle efficiency criteria for a bio-diesel mixture (B30, B50), exhaust emissions, autopower exhaust emission control in a catalytical converter, manufacture of a catalytic converter and experimental process using an aluminium group based metal catalyst.